Ageism in the Workplace: The Workers’ Explicit Attitude and Organisational Practice in Chinese First-class Cities - Tang, Liangying (2018)
The objective of this paper is to investigate the workers’ explicit attitude towards the old people and the organisational ageism behaviour in China. Since China is the country with the most elderly population in the world, it is necessary for the society and government pay more attention on the old people. In order to protect living standards of the elderly, make full use of human resources and alleviate the demographic aging, China has postponed the retirement age and implemented the two-child policy. However, it seems that the older workers are still been treated unfairly in the workplaces. In order to know more about ageism in China, this research collected data from 170 respondents by questionnaire in the Chinese first-class cities. Specifically, this research use the Fraboni Scale of Ageism (FSA) to test the workers’ explicit attitude to the old people in organisations. And the organisational behaviour of ageism have been tested as well. Finally, the research use correlation analysis and regression analysis to find the relationships between the workers’ attitude of older people and the organisational behaviour. The results found that there is no ageism in China, but the older workers have suffered unfair treatment in their organizations in the perspectives of training, promotion, employment, and workload. Furthermore, ageism has a negative influence on the organisational behaviour especially in the perspectives of the older workers’ status, salary and welfare.